Fundamental properties of Ca²⁺ signals - Thurley, Kevin; Skupin, Alexander; Thul, Ruediger; Falcke, Martin (Elsevier, 2011)
Background Ca²⁺ is a ubiquitous and versatile second messenger that transmits information through changes of the cytosolic Ca²⁺ concentration. Recent investigations changed basic ideas on the dynamic character of Ca²⁺ signals and challenge traditional ideas on information transmission. Scope of review We present recent findings on key characteristics of the cytosolic Ca²⁺ dynamics and theoretical concepts that explain the wide range of experimentally observed Ca²⁺ signals. Further, we relate properties of the dynamical regulation of the cytosolic Ca²⁺ concentration to ideas about information transmission by stochastic signals. Major conclusions We demonstrate the importance of the hierarchal arrangement of Ca²⁺ release sites on the emergence of cellular Ca²⁺ spikes. Stochastic Ca²⁺ signals are functionally robust and adaptive to changing environmental conditions. Fluctuations of interspike intervals (ISIs) and the moment relation derived from ISI distributions contain information on the channel cluster open probability and on pathway properties. General significance Robust and reliable signal transduction pathways that entail Ca²⁺ dynamics are essential for eukaryotic organisms. Moreover, we expect that the design of a stochastic mechanism which provides robustness and adaptivity will be found also in other biological systems. Ca2 + dynamics demonstrate that the fluctuations of cellular signals contain information on molecular behavior. This article is part of a Special Issue entitled Biochemical, biophysical and genetic approaches to intracellular calcium signaling. Highlights ► We review recent findings on key characteristics of cytosolic Ca²⁺ dynamics. ► We demonstrate the importance of the hierarchal arrangement of Ca²⁺ release sites. ► New theoretical concepts exploit emergent behavior of cellular Ca²⁺ spikes. ► We relate the dynamical regulation of [Ca²⁺] to information transmission. ► Stochastic Ca²⁺ signals are functionally robust and adaptive to changing conditions.